2004
DOI: 10.2139/ssrn.567081
|View full text |Cite
|
Sign up to set email alerts
|

Incentives and Information Exchange in International Taxation

Abstract: The exchange of taxpayer-specific information between national tax authorities has recently emerged as a key and controversial topic in international tax policy discussions, most notably with the OECD's harmful tax practices project and the EU's savings tax initiative. This paper analyses the effects of information exchange and withholding taxes, recognizing that countries which agree to exchange information do not forfeit the ability to levy withholding taxes, and also focusing in particular on the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 16 publications
2
27
2
1
Order By: Relevance
“…Depending on functional forms and in particular how the various semi-elasticities vary with tax rates, the picture could be more complicated than this in that the latter three regimes could be encountered more than once, as progresses. However, the saving-investment tax wedge perceived to maximize revenue in the non-cooperative regime with saving taxation will always lie in the second regime, 10 and the same therefore goes for some neighborhood around it (in particular to the left of it). In addition, there will always be a neighborhood of tax wedges to the right of =e v (where the saving tax part is only slightly bigger than zero) belonging to the third regime.…”
Section: When Is the Loss Of Saving Taxes Welfare-enhancing?mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on functional forms and in particular how the various semi-elasticities vary with tax rates, the picture could be more complicated than this in that the latter three regimes could be encountered more than once, as progresses. However, the saving-investment tax wedge perceived to maximize revenue in the non-cooperative regime with saving taxation will always lie in the second regime, 10 and the same therefore goes for some neighborhood around it (in particular to the left of it). In addition, there will always be a neighborhood of tax wedges to the right of =e v (where the saving tax part is only slightly bigger than zero) belonging to the third regime.…”
Section: When Is the Loss Of Saving Taxes Welfare-enhancing?mentioning
confidence: 99%
“…The elimination of the saving tax then reduces this excess taxation, and thus can be welfare-enhancing. 10 It is easily seen that the revenue maximizing tax wedge x s is given by 1=e u + 1=e v + p(1 )=(e u e v ) and satis…es (4.3).…”
Section: When Is the Loss Of Saving Taxes Welfare-enhancing?mentioning
confidence: 99%
“…However, some authors have recently tried to identify circumstances in which it would indeed be in the mutual interest of source and residence countries to engage in systematic international information exchange (see, e.g., Bacchetta and Espinosa (2000), Eggert and Kolmar (2002), Huizinga and Nielsen (2003), and Keen and Ligthart (2006)). In particular, Keen and Ligthart (op.cit.…”
Section: Can Taxes On Saving Be Enforced?mentioning
confidence: 99%
“…By giving some of the additional earned tax revenue through information sharing, residence countries create an incentive for source countries to share their information. This regime is analysed in Keen and Ligthart (2006b), taking into account asymmetry in size, and it is concluded that it may be in the best interest of large countries to share some of their proceeds from information exchange with small countries to make sure that the latter gain from sharing information and will hence voluntarily exchange information.…”
Section: -Problems With and Criticisms Of The Residence Principlementioning
confidence: 99%